Metrópolis y diversidad sexual: una reflexión diagonal y latinoamericana - Almeida, Vinicius Santos; Larreche, José Ignacio (El Colegio de México A.C., 2023)
In Latin America, sexual diversity has been absent in the reflection on the metropolitan until the current century, with the exception of a few publications. In this sense, the following pages want to review the particularities of this issue in some big southern cities from a spatial and sociocultural view. In this purpose, diagonal perspective of the urban territory is coined based on symbolic anchors, offering examples that emerge from the bibliographic analysis and a research in São Paulo. As a result, urbanity as an entry key to think about a resignified urban geography.